Total Pelvic Exenteration in Leiomyosarcoma - A Case Report - Sarkar, Atanu; Rai, Shweta; Singh, Angad; Ghosh, Joydeep; Bhaumik, Jaydip (Indian Journal of Medical and Paediatric Oncology, 2020)
Locally advanced high-grade leiomyosarcomas (LMS) with visceral involvement are difficult to manage. Here, we present a case of locally advanced high-grade sarcoma where total pelvic exenteration was undertaken to achieve complete cytoreduction. A 54-year-old lady with a prior history of hysterectomy and bilateral salpingoophorectomy done 8 years back for heavy menstrual bleeding presented to us with an abdomino-pelvic mass. Magnetic resonance imaging of the abdomen suggested large heterogeneous pelvic mass displacing urinary bladder anteriorly and abutting recto-sigmoid posteriorly with no luminal involvement. There was bilateral hydronephrosis. Computed tomography of the thorax revealed no evidence of metastatic disease. A review of previous biopsy and a repeat ultrasound-guided biopsy from the pelvic mass done at our institute suggested spindle-cell neoplasm. In view of pelvis confined disease in a young woman with well-preserved general condition, decision for surgical excision was taken. She underwent total pelvic exenteration with en bloc removal of mass, bladder, and involved portion of recto-sigmoid as the disease was infiltrating both the bladder and the recto-sigmoid. Her postoperative course was turbulent, but she recovered fully and was discharged 20 days after surgery. The operative specimen histopathology revealed high-grade LMS. She received four cycles of adjuvant chemotherapy and thereafter was kept on follow-up. Although she was clinically doing well, her general condition never improved beyond Eastern cooperative oncology Group 2. She also had persistent depressive symptoms. After 14 months of completion of treatment, she recurred with a huge abdominal disease. In view of her general condition and huge disease volume, decision was taken for supportive care only. LMS in advanced stages are difficult to manage. Even after aggressive management with radical exenterative surgery and chemotherapy, we could achieve only temporary control of locally advanced LMS.
Keywords: Chemotherapy; exenteration; extrauterine; leiomyosarcoma